1983
DOI: 10.1128/jb.155.1.357-366.1983
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation of Streptomyces griseus in submerged culture

Abstract: A wild-type strain of Streptomyces griseus forms spores both on solid media (aerial spores) and in liquid culture (submerged spores). Both spore types are highly resistant to sonication, but only aerial spores are resistant to lysozyme digestion. Electron micrographs suggest that lysozyme sensitivity may result from the thinner walls of the submerged spores. Studies of the life cycle indicate that neither streptomycin excretion nor extracellular protease activity is required for sporulation; the analysis of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 19 publications
(26 reference statements)
0
45
0
Order By: Relevance
“…It can be concluded that S. anulatus JH801 is among the few Streptomyces strains that sporulate in submerged cultures (the first Streptomyces strain to show submerged sporulation, S. griseus, was found by Kendrick and Ensign (1990)). In general, Streptomyces strains sporulate relatively easily on solid media, with no special medium requirements reported (Glazebrook et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that S. anulatus JH801 is among the few Streptomyces strains that sporulate in submerged cultures (the first Streptomyces strain to show submerged sporulation, S. griseus, was found by Kendrick and Ensign (1990)). In general, Streptomyces strains sporulate relatively easily on solid media, with no special medium requirements reported (Glazebrook et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites would be produced by the substrate mycelium at the stationary phase after a transient growth arrest (Granozzi et al, 1990;Neumann et al, 1996;Novotna et al, 2003;Zhou et al, 2005;Chouayekh et al, 2007). Despite that, sporulation was reported in liquid cultures for several streptomycetes, such as Streptomyces venezuelae (Glazebrook et al, 1990), S. griseus (Kendrick & Ensign, 1983), Streptomyces chrysomallus (Kuimova & Soina, 1981), S. antibioticus ETHZ7451 (Novella et al, 1992), Streptomyces albidoflavus SMF301 (Rho & Lee, 1994), or Streptomyces brasiliensis (Rueda et al, 2001). Sporulation was also seen to be activated in several Streptomyces species under nutritional downshifts, including the model strain S. coelicolor (Koepsel & Ensign, 1984;Daza et al, 1989), and was also observed in several streptomycetes liquid cultures during the screening experiments aimed at discovering novel secondary metabolites (Yag€ ue P, Genilloud O, Manteca A, unpublished results).…”
Section: Differentiation and Development Of Streptomyces In Liquid Cumentioning
confidence: 99%
“…Streptomycetes are aerobic gram-positive soil bacteria that grow as multinucleoidal, multicellular, branched filaments and undergo morphological and physiological differentiation in response to environmental factors (Kendrick & Ensign, 1983;Champness & Chater, 1994;Chater, 1998;Keijser et al, 2002). The first sign of morphological differentiation is the formation of aerial sporogenic hyphae, which give a fuzzy, white appearance to the colonies.…”
Section: Sporulation In Streptomyces Involves Iclr Family Membersmentioning
confidence: 99%